Breaking silences in the Aftermath of Holocaust trauma in Elie Wiesel's Day. Issue 3 (3rd July 2021) - Levin, Adam
ABSTRACT: This article employs a close reading of Elie Wiesel's third novel, Day (1961), as a lens through which to explore the difficulties inherent in disengaging from the Holocaust past and their impact on the Holocaust survivor's efforts to live in the present. In particular, The article explores how the novel's narrative employs silence, a key Wieselian symbol, in constructing its overarching framework. These textual silences, I suggest, portray the text's protagonist's inability to escape his past at the camps. It is only through transforming these silences into speech that he is able to truly begin to live in the present.